The study of prognostic significance of CA 15-3 in breast cancer - Gupta, Shankar Kumar; Kumar, Vinod; Anees, Afzal; Goel, Arjun (International Surgery Journal, 2018)
Background: Cancer Antigen 15-3 (CA 15-3) is a tumour-associated antigen used as serum marker for breast cancer surveillance in patients and for monitoring the response to treatment. Aim of this study was to prospectively evaluate CA 15-3 as a prognostic factor in early detection of breast cancer relapse, recurrence and early detection of distant metastasis as well as to analyse the statistical correlation between CA 15-3 levels and clinical-pathological parameters including tumour size, lymph node, histological type, grading, hormonal receptors. Methods: Sera of 85 women with breast carcinoma obtained pre-treatment, post-treatment and follow-up at 6 months were assayed for CA 15-3 by solid phase enzyme-linked immunosorbent assay (ELISA). Results: Author founds that the mean serum CA 15-3 levels in patients before treatment were significantly higher (50.59U/ml) compared with those of CA 15-3 after treatment (24.07U/ml) and follow-up at 6 months (21.07U/ml). Author also found that elevated pre-treatment serum levels of CA 15-3 were significantly correlated with poor prognosis of patients. In particular, among 16/85 patients (18.8%) that displayed over cut-off (>24.95U/ml) pre-treatment levels of CA 15-3, 2 patients (2.35%) developed recurrence,2 patients (2.35%) developed residual tumour, 2 patients (2.35%) developed advanced disease (metastases to distant sites) and 10 (11.76%) patients expired during and after study. Chi-square correlation analysis revealed that the presences of increased serum levels of CA 15-3 after treatment are significant risk factors for poor prognosis in patients. Conclusions: Elevated pre-treatment concentrations of CA 15-3 may be a useful prognostic factor for cancer progression in patients.